Construction of Arrangements for Limiting the Liability of Debtors and Individual Guarantors for Acts of Abuse of Circumstances in Debt and Receivables Agreements - Sihotang, Biner (Journal of Law, Politic and Humanities, 2024)
Article 33 paragraph (4) of the Constitution of the Republic of Indonesia of 1945 is a moral message and a cultural message in the constitution of the Republic of Indonesia in the field of economic life, including related to guarantors in debt and receivables agreements regulated in Articles 1820 to 1850 of the Civil Code with the provision that the guarantor is obliged to pay off the debtor's debt to the creditor if the debtor has run out of assets to pay his debts. In practice, the privilege, which is the privilege of the guarantor, is not easy to apply with an act of abuse of circumstances, so that the privilege of the guarantor can be released which results in uncertainty of the limitation of the guarantor's responsibility for the debtor's debt. The problem in this study is how to regulate the limits of legal liability of debtors and individual guarantors in debt and receivables agreements in Indonesia? How is the construction of the regulation of limiting the liability of debtors and individual guarantors in the future for acts of abuse of circumstances in debt and receivables agreements. This research method is normative using secondary data, and analyzed using qualitative descriptive analysis. The results of the study show that the construction of the regulation of limiting the liability of debtors and individual guarantors in the future for acts of abuse of circumstances in the debt and receivables agreement is that the guarantor only bears the principal and interest, with the provision that the creditor is obliged to confiscate and sell the debtor's goods first. This is because the characteristic of debt is the amount of payments made in each period consisting of interest and principal of debt. Therefore, there is a need for a Financial Services Authority Regulation that prohibits banks from making clauses in the guarantee agreement to release their privileges, as well as judicial review of Articles 1820, 1831, 1832 number 1 and Article 1833 of the Civil Code at the Constitutional Court related to the release of Guarantor's privileges is contrary to the 1945 Constitution of the Republic of Indonesia and does not have binding legal force.